1971
DOI: 10.1159/000136195
|View full text |Cite
|
Sign up to set email alerts
|

Species Differences in the Binding of Phenylbutazone to Plasma Albumin

Abstract: The binding of phenylbutazone to plasma albumins from man, rat, rabbit and dog has been measured at 37°C by equilibrium dialysis. Species differences were found both in the number of phenylbutazone binding sites per albumin molecule and the affinity of such sites for the drug. Using the binding parameters from this study we have shown how it is possible to estimate the effect of plasma albumin binding on the distribution of a drug in the body. These calculations suggest that although phenylbutazone has a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Thus, the binding of acetriozate [1,2,4] and phenylbutazo'ne [11 ] is enhanced and concomitantly with the latter observation flufenamic acid binding is decreased.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the binding of acetriozate [1,2,4] and phenylbutazo'ne [11 ] is enhanced and concomitantly with the latter observation flufenamic acid binding is decreased.…”
Section: Discussionmentioning
confidence: 84%
“…A number of published articles have discussed interspecies variations in the tissue distribution of organic chemicals . These variations have been shown to depend upon a number of factors, including differences in tissue composition, plasma protein binding, tissue DNA concentrations, and active transporter specificities and affinities . These studies support the need for the use of species‐specific K t:pl values for PBPK modeling and risk assessment applications.…”
Section: Introductionmentioning
confidence: 91%
“…Detailed warfarin and phenylbutazone binding studies by the use fluorescence, absorption spectrometry and near-UV circular dichroism showed that the both of the ligands bind with high-affinity to a region in subdomain IIA [ 5 , 22 , 35 , 54 , 55 ]. The X-ray crystalographic analysis of warfarin–HSA and phenylbutazone–HSA complexes provided the more information about the interactions between those drugs and HSA in binding site.…”
Section: Resultsmentioning
confidence: 99%